PROJECT CERITA – A PEACEBUILDING INITIATIVE THROUGH STORYTELLING - Wulandari, Roosalina (Bina Nusantara University, 2019)
The rising intolerance in Indonesia is spiking and has become more confounding due to the heated political temperature following series of recent national elections. Religious identity is politicized in a magnitude that escalates religious fundamentalism and consequently, intolerance. Past research shown how personal uncertainty enable individuals to find closure through firm beliefs and ideologies. This article is aimed to understand how religious intolerance function as a coping mechanism towards perceived threats of challenged worldviews, and how it potentially strengthened when supported collectively. The paper aim to focus on efforts made in the area of promotion of tolerance and inclusivity, understanding the complexity of identity helps peacebuilding initiatives to manage religious intolerance. The paper will then highlight Project CERITA (Community Empowerment for Raising Inclusivity and Trust through Technology Application), a peacebuilding program initiated by The Habibie Center that conducted storytelling and dialog facilitation workshop in six cities in Indonesia to promote peace and counter religious intolerance.